Plasticity in the sensorimotor cortex induced by Music-supported therapy in stroke patients: a TMS study - Grau-Sánchez, Jennifer; Amengual, Julià L.; Rojo, Nuria; Veciana de las Heras, Misericòrdia; Montero, Jordi; Rubio, Francisco; Altenmüller, Eckart; Münte, Thomas F.; Rodriguez-Fornells, Antoni (Frontiers in Human Neuroscience, 2013)
Playing a musical instrument demands the engagement of different neural systems. Recent studies about the musician's brain and musical training highlight that this activity requires the close interaction between motor and somatosensory systems. Moreover, neuroplastic changes have been reported in motor-related areas after short and long-term musical training. Because of its capacity to promote neuroplastic changes, music has been used in the context of stroke neurorehabilitation. The majority of patients suffering from a stroke have motor impairments, preventing them to live independently. Thus, there is an increasing demand for effective restorative interventions for neurological deficits. Music-supported Therapy (MST) has been recently developed to restore motor deficits. We report data of a selected sample of stroke patients who have been enrolled in a MST program (1 month intense music learning). Prior to and after the therapy, patients were evaluated with different behavioral motor tests. Transcranial Magnetic Stimulation (TMS) was applied to evaluate changes in the sensorimotor representations underlying the motor gains observed. Several parameters of excitability of the motor cortex were assessed as well as the cortical somatotopic representation of a muscle in the affected hand. Our results revealed that participants obtained significant motor improvements in the paretic hand and those changes were accompanied by changes in the excitability of the motor cortex. Thus, MST leads to neuroplastic changes in the motor cortex of stroke patients which may explain its efficacy.